A polgármester, a falu meg a közösség: hozzászólás a „független” polgármester vitához - Borboly, István; Csite, András (Tér és Társadalom, 1999)
In our study with 31 interview with mayors in villages we made an attempt to approach at frame, where politicising is appeared in village. The problems of politicising in village are approached with key concept of mayors’ talking. The most important factor is „independence" which means independence of both parties and „high policy" dominated by parties. The assumption of the different social structure between village and city – and above all between village and the capital – and the differentiation between the mayor and the „national" politic is emerged in this isolation. Mayors are applying the language discursive strategy of political representatives explored by Bourdieu: they establish the homogenous group of people being represented, they appear as a representative of the group and themselves are dissolved in the „we" of the group. The difference between them and „national/party" politic is that the created group doesn’t mean a „larger" group (layer, class, nationality, citizen, etc.), but it connects to the existence of village, as a type of settlement.